Primate Locomotion 2010
DOI: 10.1007/978-1-4419-1420-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Limb Structural Properties in Free-ranging Chimpanzees from Kibale, Gombe, Mahale, and Taï Communities

Abstract: Structural characteristics of limbs bones provide insight into how an animal dynamically loads its limbs during life. Cause-and-effect relationships between loading and the osteogenic response it elicits are complex. In spite of such complexities, cross-sectional geometric properties can be useful indicators of locomotor repertoires. Typical comparisons use primates that are distinguished by broad habitual locomotor differences, usually with samples garnered from several museum collections. Intraspecific varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…This is likely due to generally similar locomotor patterns among subspecies (Doran and Hunt, 1994;Sarringhaus et al, 2014). Differences in shape have been found in chimpanzees living in different communities, but no definitive relationships emerged between shape and locomotor mode (Carlson et al, 2006(Carlson et al, , 2011. At the species level, midshaft femoral and humeral shapes differ between gorillas and chimpanzees, with a trend of increased circularity with increased levels of arboreal locomotion in the latter compared with the former (Carlson, 2005).…”
Section: Shapementioning
confidence: 78%
See 2 more Smart Citations
“…This is likely due to generally similar locomotor patterns among subspecies (Doran and Hunt, 1994;Sarringhaus et al, 2014). Differences in shape have been found in chimpanzees living in different communities, but no definitive relationships emerged between shape and locomotor mode (Carlson et al, 2006(Carlson et al, , 2011. At the species level, midshaft femoral and humeral shapes differ between gorillas and chimpanzees, with a trend of increased circularity with increased levels of arboreal locomotion in the latter compared with the former (Carlson, 2005).…”
Section: Shapementioning
confidence: 78%
“…Relating specific locomotor behaviors to bone shape has been difficult in adult great apes and other primates, who have diverse locomotor repertoires and regularly move in a variety of ways (Ruff and Runestad, 1992;Carlson, 2005;Carlson et al, 2006Carlson et al, , 2011Patel et al, 2013). No difference in humeral or femoral midshaft shape (I max / I min ) was found among chimpanzee subspecies in an analysis of adult specimens (Carlson, 2005).…”
Section: Shapementioning
confidence: 81%
See 1 more Smart Citation
“…Several studies have also evaluated whether cross‐sectional shape, another variable of a long bone's cross‐sectional geometry, can serve as a correlate of a long bone's mechanical loading history (Carlson, ; Carlson et al, ; Carlson and Judex, ; Simons, , Simons et al, ; see also Demes, for alternative arguments). Specifically, these studies have tried to test the general hypothesis that cross‐sectional shape reflects whether an animal's long bones have experienced relatively uniform or variable (i.e., multidirectional) loading regimes and bending moments.…”
mentioning
confidence: 99%
“…For example, analyses of cross‐sectional shape using I max / I min ratios suggest that a suspensory (and more arboreal) signal (i.e., ratios closer to 1.0) may be present in humeri of chimpanzees ( Pan ) compared with a more quadrupedal (and more terrestrial) signal (i.e., ratios deviating from 1.0) observed in closely related gorillas ( Gorilla ) (see Table in Carlson, ). Subsequent studies of humeral cross‐sectional shape, however, have demonstrated fewer significant differences within and between individuals, sexes, and populations of wild chimpanzees with specific documented positional behavioral data (Carlson et al, ) or between wild and captive chimpanzees that most likely differed in positional behaviors, as well as substrate use, diet, and so forth (Morimoto et al, ). Thus, while long bone cross‐sectional shape as measured from the ratio of I max and I min could be used to aid in distinguishing more general locomotor behaviors and substrate preferences (e.g., arboreal or terrestrial; quadrupedal or suspensory), it may be more difficult to distinguish between specific locomotor categories (e.g., scrambling, bridging, and climbing; Carlson, ; Carlson et al, ).…”
mentioning
confidence: 99%